Reappraisal of Gestational Weight Gain Recommendations in Obese Pregnant Women: A Population-Based Study of 337,590 Births - Devlieger, Roland (Obes Facts, 2020)
BACKGROUND AND OBJECTIVE: Maternal obesity is an epidemic health problem that is aggravated by excessive gestational weight gain (GWG) and postpartum weight retention. Current US Institute of Medicine (now US National Academy of Medicine) guidelines (2009) for GWG need to be evaluated against the current rise in obesity in the general and pregnant population. We wanted to study the relation between GWG and pregnancy and birth outcomes and to relate this to the current recommendations for GWG. METHODS: Population-based study. We performed an epidemiological analysis in a cohort of Belgian pregnant women with singleton live births at term (≥37 weeks) between 2009 and 2014 (n = 337,590). Logistic regression was used to determine the optimal GWG in relation to relevant pregnancy and birth outcomes. RESULTS: The prevalence of maternal obesity significantly increased from 10.3% in 2009 to 11.4% in 2014. The mean (SD) body mass index at the start of the pregnancy significantly increased from 23.9 (4.5) in 2009 to 24.2 (4.6) in 2014. Excessive GWG was frequent, especially in overweight (56.8%) and obese (52.9%) pregnant women. In the logistic regression model, the amount of GWG associated with the lowest incidence of both large-for-gestational-age and small-for-gestational-age infants was 21 kg in underweight women, 14 kg in normal weight, 8 kg in overweight, 0 kg in obese class I, −4 kg in obese class II and −5 kg in obese class III. CONCLUSION: The prevalence of maternal obesity has risen in Belgium between 2009 and 2014. Current GWG guidelines, based on historic observational data, are probably too liberal for class II and III obese women in which better outcomes are being predicted for lower weight gain than recommended.